A review of health promotion funding for older adults in Europe: a cross-country comparison. Issue 5 (August 2016) - Arsenijevic, Jelena; Groot, Wim; Tambor, Marzena; Golinowska, Stanislawa; Sowada, Christoph; Pavlova, Milena
Abstract Background Health promotion interventions for older adults are important as they can decrease the onset and evolution of diseases and thus can reduce the medical costs related to those diseases. However, there is no comparative evidence on how those interventions are funded in European countries. The aim of this study is to explore the funding of health promotion interventions in general and health promotion interventions for older adults in particular in European countries. Method We use desk research to identify relevant sources of information such as official national documents, international databases and scientific articles. Fora descriptive overview on how health promotion is funded, we focus on three dimensions: who is funding health promotion, what are the contribution mechanisms and who are the collecting agents. In addition to general information on funding of health promotion, we explore how programs on health promotion for older population groups are funded. Results There is a great diversity in funding of health promotion in European countries. Although public sources (tax and social health insurance revenues) are still most often used, other mechanisms of funding such as private donations or European funds are also common. Furthermore, there is no clear pattern in the funding of health promotion for different population groups. This is of particular importance for health promotion for older adults where information is limited across European countries. Conclusions This study provides an overview of funding of health promotion interventions in European countries. The main obstacles for funding health promotion interventions are lack of information and the fragmentation in the funding of health promotion interventions for older adults.